A Relational Perspective on Turnover: Examining Structural, Attitudinal, and Behavioral Predictors - Mossholder, Kevin W.; Settoon, Randall P.; Henagan, Stephanie C. (Academy of Management Journal, 2005)
This study examined whether structural, attitudinal, and behavioral variables of a relational nature were predictive of employee turnover. Participants were a sample of 176 health care employees from a large public medical center. Using survival analysis over a five-year time frame, we found that two such variables, network centrality and interpersonal citizenship behavior, predicted turnover. Implications of taking a relational perspective toward turnover and other withdrawal behaviors found in organizations are discussed.